Reader Response: Teaching NeuroImage: Palindromic Rheumatoid Meningitis: A Tale of 2 Hemispheres. (8th February 2022) - Hung, Sheng-Che
Abstract : Thank you for sharing this interesting case. 1 Pachymeningeal enhancement refers to dura-arachnoid enhancement, which mainly occurs adjacent to the inner table of the skull. The pattern of meningeal enhancement, in this case, would not be pachymeningeal enhancement but would be better described as leptomeningeal enhancement. 2 Leptomeningeal enhancement follows the pial surface of the brain and fills the subarachnoid spaces of the sulci and cisterns.